MXRA8 is an immune-relative prognostic biomarker associated with metastasis and CD8+ T cell infiltration in colorectal cancer - Tan, Lulu; Fu, Daan; Liu, Feng; Liu, Jia; Zhang, Yang; Li, Xin; Gao, Jinbo; Tao, Kaixiong; Wang, Guobin; Wang, Lin; Wang, Zheng (Frontiers in Oncology, 2023)
Background: Colorectal cancer (CRC) is the second most common cause of cancer-related deaths worldwide. Tumor metastasis and CD8+ T cell infiltration play a crucial role in CRC patient survival. It is important to determine the etiology and mechanism of the malignant progression of CRC to develop more effective treatment strategies. Methods: We conducted weighted gene co‐expression network analysis (WGCNA) to explore vital modules of tumor metastasis and CD8+ T cell infiltration, then with hub gene selection and survival analysis. Multi-omics analysis is used to explore the expression pattern, immunity, and prognostic effect of MXRA8. The molecular and immune characteristics of MXRA8 are analyzed in independent cohorts, clinical specimens, and in vitro. Results: MXRA8 expression was strongly correlated with tumor malignancy, metastasis, recurrence, and immunosuppressive microenvironment. Furthermore, MXRA8 expression predicts poor prognosis and is an independent prognostic factor for OS in CRC. Conclusion: MXRA8 may be a potential immunotherapeutic and prognostic biomarker for CRC.